Innovative digital rock music processing tools as an approach to upgrading the alternative music industry - Martynenko, Mykola Serhiiovych (Global Prosperity, 2025)
Abstract. The need to transform approaches to processing musical works is explained by the total digitalization of the cultural and artistic field. The purpose of the article is to analyze the potential advantages and challenges of integrating digital technologies into the process of processing rock music. The study analyzes the potential of digital transformation of the music sphere and substantiates that the upgrade of the alternative sphere of the music industry contributes to the expansion of the conceptual vision of rock music. The specifics of the integration of immersive technologies of virtual and mixed reality in the context of interactive experience, simulation of concert performances and immersion in an authentic musical environment are investigated. It has been proven that current trends in the development of digital systems in the music field are aimed at personalizing the creative process, creativity and efficiency, which is achieved by involving online collaboration, mobile applications, computer programs for creating music, virtual musical instruments, digital scores and applications for developing hearing and rhythm, as well as adaptive technologies, artificial intelligence and social networks.